Factor substitution, income distribution, and growth in a generalized neoclassical model - Irmen, Andreas; Klump, Rainer (Discussion paper series, 2007)
We analyze a generalized neoclassical growth model that combines a normalized CES production function and possible asymmetries of savings out of factor incomes. This generalized model helps to shed new light on a recent debate concerning the impact of factor substitution and income distribution on economic growth. We can show that this impact relies on both an efficiency and an acceleration effect, where the latter is caused by the distributional consequences of an increase in the elasticity of substitution. While the efficiency effect is always positive, the direction of the acceleration effect depends on the particular savings hypothesis. However, if savings out of capital income are substantial so that a certain threshold value is surpassed we find that the efficiency effect dominates so that higher factor substitution can work as a major engine of growth.